Previous hepatitis E virus infection, cirrhosis and insulin resistance in patients with chronic hepatitis C - Bricks,Guilherme (2019)
ABSTRACT Background: Hepatitis E virus (HEV) infection in patients with pre-existing liver disease has shown high morbidity and lethality. The consequences of HEV superinfection in patients with chronic hepatitis C virus (HCV) infection are not fully understood. This study aimed to evaluate the association between the presence of anti-HEV antibodies, liver cirrhosis, and insulin resistance. Methods: A total of 618 patients chronically infected with HCV were included from three reference centers for viral hepatitis in São Paulo, Brazil. Presence of anti-HEV IgG was assessed by enzyme-linked immunosorbent assay (WANTAI HEV-IgG ELISA). Results: The seroprevalence of anti-HEV in patients with cirrhosis was significantly higher than in patients without cirrhosis (13.2% vs 8%, OR = 1.74, p = 0.04). Seropositivity for anti-HEV, adjusted for sex, age, and HCV genotype showed an association trend with hepatic cirrhosis (aOR = 1.75, p = 0.059). Presence of HEV antibodies, adjusted for age, body mass index and cirrhosis, was shown to be independently associated with insulin resistance (aOR: 4.39; p = 0.045). Conclusion: Patients with chronic hepatitis C are under risk of hepatitis E virus superinfection in Brazil. The trend toward association between cirrhosis and previous HEV infection suggests that it may accelerate liver fibrosis in patients with chronic hepatitis C. In addition, previous infection by HEV is independently associated with insulin resistance in the studied population, which may be an extra-hepatic manifestation of hepatitis E that persists after resolution of the active infection, and may contribute to fibrosis progression.